2018
DOI: 10.5603/gp.a2018.0117
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and the eye. Changes in morphology of the cornea and the anterior chamber of the eye in pregnant woman

Abstract: Objectives:The main goal of the study was to determine whether uncomplicated pregnancy and natural labor exert influence on the cornea and the anterior chamber of the eye. Material and methods:The study included 114 eyes of 57 women in age of 21-35 years old. Only patients in the physiological pregnancy and giving natural birth were recruited into study.Prospective observative examination was performed. Patients were diagnosed twice: in 36 HBD and 6 weeks after labor. Using the Scheimpflug camera (Pentacam sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…According to Akar, et al (2005, p. 41), "no significant change in mean keratometry or refractive error values was observed in pregnant women and controls during the study". Studies by Taradaj, et al (2018) did not find a relationship between pregnancy and cylindrical refractive error and the axis of astigmatism.…”
Section: Refractive Errors During Pregnancy: a Bibliographic Reviewmentioning
confidence: 82%
“…According to Akar, et al (2005, p. 41), "no significant change in mean keratometry or refractive error values was observed in pregnant women and controls during the study". Studies by Taradaj, et al (2018) did not find a relationship between pregnancy and cylindrical refractive error and the axis of astigmatism.…”
Section: Refractive Errors During Pregnancy: a Bibliographic Reviewmentioning
confidence: 82%
“…Mete et al found that the valsalva maneuvers reduce it by anterior displacement of iridolenticular diaphragm during this exercise [17]. Pregnancy was found to vary ACD in the third trimester versus postpartum period; these changes were not statistically significant, but the changes were attributed to CT change as a response to stromal water retention by hormonal effect [18]. For many years, the question remained if low birth weight was related to adulthood modifications in anterior chamber geometry.…”
mentioning
confidence: 89%
“…The skin changes were speculated to be associated with hormone-mediated water retention ( Eisenbeiss et al, 1998 ). In some pregnant females, pregnancy-associated changes in cornea thickness have been reported, presumably due to water retention that is reversed postpartum ( Taradaj et al, 2018 ). As changes in water content would be a readily reversible strategy to influence the properties of a connective tissue, it would be preferred over one that involved the degradation and synthesis of an essential structural component such as collagen.…”
Section: Influence Of Sex On Msk Tissues As An Adultmentioning
confidence: 99%